A protocol for a critical realist synthesis of school mindfulness interventions designed to promote pupils’ mental wellbeing - Abbott, Pamela; Nixon, Graeme; Stanley, Isabel; D’Ambruoso, Lucia (Frontiers in Public Health, 2024)
Introduction The review described in this protocol will be the first critical realist review of the literature reporting on the impact of school-based mindfulness interventions on the mental wellbeing of pupils. Mindfulness interventions are increasingly being introduced into schools to promote children’s (and teachers’) wellbeing. Findings from impact evaluations, including systematic reviews and metanalysis, suggest that school-based mindfulness interventions promote pupils’ wellbeing. However, there is a need for further evidence on the underlying causal mechanisms and contexts that explain program outcomes, to provide insight into how mindfulness programs can be successfully implemented in other contexts. Methods and analysis A critical realist review methodology will be used to provide a causal interdisciplinary understanding of how school-based mindfulness interventions promote the mental wellbeing of pupils. This will be done through a systematic literature review and extrapolating context, agency, intervention, mechanisms, and outcome configurations. This will enable an understanding of how, in certain contexts, pupils can use the resources offered by a mindfulness intervention knowingly or unknowingly to trigger mechanisms that promote their mental wellbeing and what mechanisms in the context support, restrict or prevent change. We will then use retrodiction and retroduction to develop the most plausible interdisciplinary middle-range theory to explain the findings. Discussion The review findings will inform a critical realist evaluation of a mindfulness intervention in schools. The findings from the review will also enable us to inform policymakers and other stakeholders about what conditions need to be in place for mindfulness interventions to promote pupils’ mental wellbeing. We will publish the findings from the review in academic and professional publications, policy briefs, workshops, conferences, and social media. PROSPERO registration number: CRD42023410484.